Effect of Plant Extracts on Root Knot Nematode Meloidogyne incognita (Kofoid & White) Chitwood in Jaffna, Sri Lanka - Sujavanthi, L.; Nirosha, A.; Mikunthan, G. (University of Jaffna, 2020)
Root-knot nematode, Meloidogyne incognita is one of the major pests in tomato and it forms galls in plant roots leading to growth retardation and wilting. This study was aimed to manage M. incognita using plant extracts as an alternative to the application of synthetic chemicals. Leaves of locally available underutilized plants such as Ocimum basilicum, Moringa oleifera, Aegle marmelos, Cassia fistula and Azadirachta indica were tested against M. incognita. During the in vitro experiment, M. incognita second stage juveniles were exposed to 25%, 50% and 100% concentrations of aqueous extracts of plant leaves. The results revealed that 100% concentration of plant extracts at 48 hours exposure was highly toxic against the survival of M. incognita second stage juveniles than other concentration of plant extracts and exposure time. Maximum mortality (90.25%) was achieved in 100% of A. marmelos after 48 hours of time. In pot experiment all the plant extracts showed promising results inhibiting gall formation with varying degrees which was statistically significant (p<0.05). The extent of galls in M. oleifera was significantly less (12.33) in plant extracts treatments (p<0.05). The highest shoot height of tomato was achieved in M. oleifera (19.33±0.71cm), followed by A. indica (15.97±0.49cm), C. fistula (15.87±0.55cm), A. marmelos (14.43±1.03cm) and O. basillicum (12.23±0.84cm), receptively. Plant extracts treated tomato showed significantly higher root length whereas maximum root length of 37± 0.44cm was achieved in A. indica followed by A. marmelos (3.1± 0.2cm) (p<0.05). The study has concluded that M. oleifera leaf extract can be used for management of M. incognita. In future, investigation on the different concentrations of plant extracts on inhibition of root galls with highest shoot height and yield is suggested.
Keywords: M. incognita; Plant extracts; Root gall; knot nematode; Tomato